Komunikasi, Keberagaman, dan Pariwisata: Strategi Warga Rama Agung menuju Desa Wisata Religius - Yulizar Pramudika Tawil; Giska Mala Rahmarini (JURNAL ILMIAH SYI'AR, 2020)
Indonesia is experiencing an emergency communication between religious communities. The issue of division is easier to emerge and be consumed quickly by the community than the issue of togetherness. Interestingly, it is always the best practice of harmony between religious communities in rural areas which raises optimism that diversity in Indonesia continues. This study explains communication between religious communities in the success of the implementation of a religious tourism village in Rama Agung. A qualitative case study approach was carried out. Data were collected through interview techniques, observation, and search for relevant literature. Specifically for the interview data, we processed it through the transcript mechanism, keyword search, keyword categorization, and wording. Our findings include three important focuses: indicators of diversity, communication patterns in religious tourism villages, and forums for communication. We found three salient social capitals: the legacy of value systems brought by immigrant communities and the results of value processing in the environment, written rules or agreements between communities, and the leadership of religious leaders who were able to balance internal and external desires. Informal and formal communication forums have been used by the community to communicate their ideas. Then we present a communication pattern from the idea discussed, the development, to the execution stage. In the end, this study suggests a narrative approach to describe more clearly the way of communication in the village of religious tourism organized by religious diversity